Virtues, ecological momentary assessment/intervention and smartphone technology - Runyan, Jason D.; Steinke, Ellen G. (Frontiers in Psychology, 2015)
Virtues, broadly understood as stable and robust dispositions for certain responses across morally relevant situations, have been a growing topic of interest in psychology. A central topic of discussion has been whether studies showing that situations can strongly influence our responses provide evidence against the existence of virtues (as a kind of stable and robust disposition). In this review, we examine reasons for thinking that the prevailing methods for examining situational influences are limited in their ability to test dispositional stability and robustness; or, then, whether virtues exist. We make the case that these limitations can be addressed by aggregating repeated, cross-situational assessments of environmental, psychological and physiological variables within everyday life—a form of assessment often called ecological momentary assessment (EMA, or experience sampling). We, then, examine how advances in smartphone application (app) technology, and their mass adoption, make these mobile devices an unprecedented vehicle for EMA and, thus, the psychological study of virtue. We, additionally, examine how smartphones might be used for virtue development by promoting changes in thought and behavior within daily life; a technique often called ecological momentary intervention (EMI). While EMA/I have become widely employed since the 1980s for the purposes of understanding and promoting change amongst clinical populations, few EMA/I studies have been devoted to understanding or promoting virtues within non-clinical populations. Further, most EMA/I studies have relied on journaling, PDAs, phone calls and/or text messaging systems. We explore how smartphone app technology provides a means of making EMA a more robust psychological method, EMI a more robust way of promoting positive change, and, as a result, opens up new possibilities for studying and promoting virtues.